The influence of intervention complexity on barriers and facilitators in the implementation of professional pharmacy services - A systematic review - Möcker, Robert; Terstegen, Theresa; Haefeli, Walter E.; Seidling, Hanna (Research in social and administrative pharmacy, 2021)
Background: Community pharmacies increasingly offer professional pharmacy services, whose implementation is often influenced by facilitating or obstructive implementation factors. The occurrence and composition of implementation factors vary among different services with discrete characteristics and complexity of the intervention, making it difficult to foresee potential barriers in implementation. Objective(s): This paper investigates potential associations between intervention complexity and occurring implementation factors. Methods: A systematic literature search on the implementation factors and intervention complexity of professional pharmacy services in the community setting was carried out in electronic databases (PubMed, CINAHL, and PsycINFO) throughout December 2018. Implementation factors were extracted from semi-structured interviews, focus groups, and surveys with community pharmacists and categorized using the Consolidated Framework for Implementation Research (CFIR). The complexity of each service was assessed using the following complexity parameters: (I) number of involved healthcare professions, (II) number of service components such as recruiting of patients, screening intervention, and follow-up, (III) frequency of the service, (IV) expenditure of time per patient (encounter), and (V) workflow distortion, i.e. booking appointments for intervention with the patient. Finally, the association between implementation factors and intervention complexity was analyzed by quantifying implementation factors and by relating them to specific intervention characteristics using Fisher's exact test. Results: 15 studies covering a broad spectrum of professional pharmacy services were included. There was a trend that in services with higher complexity more implementation factors occurred (p = 0.094). Single key complexity parameters can trigger specific implementation factors. For instance, general practitioner and pharmacy technician involvement were significantly associated with interprofessional communication and leadership engagement, respectively. Conclusion: Key implementation factors and associated complexity parameters seem to be of similar or more importance than the total number of implementation factors with regard to successful implementation. By assessing various complexity parameters of an intervention, potential key barriers could be identified and subsequently addressed prior to implementation.
Gesehen am 30.09.2021